Leveraging Dynamic Capabilities and Digital Culture for Sustainable Business Model Innovation - Hibban Al Asyim Kusuma, Fairuz; Qurrota A’yun, Annisa (Inovasi Analisis Data, 2025)
Purpose: This study examines how green dynamic capabilities mediate the relationship between organizational capabilities and sustainable business model innovation in emerging economies.Method: This research adopts a quantitative approach that is based on the cross-sectional survey data of 167 Indonesian medium to large firms. A validated structured questionnaire for data collection, involving regression analysis and bootstrapping techniques to test for direct and mediating effects.Findings: The findings reveal that Green dynamic capabilities completely mediate the links between five organizational capacities: data analytics, digital leadership, strategic agility, platform orchestration, and employee digital readiness and sustainable business model innovation. All the hypothesized paths are validated, showing that organizational capabilities underpin sustainable innovation mainly by nurturing distinctive environmental sensing, seizing, and transforming capabilities.Novelty: The present study is the first to propose green dynamic capabilities as a unique mediating construct and empirically demonstrate its significant role in linking digital transformation and sustainability goals. The study provides a new integrated model identifying how the general capabilities of organizations are transformed into sustainability outcomes in process and product through three core drivers within an emerging economy environment.Implications: This research implies that organizations need to focus on developing specialized green dynamic capabilities in addition to their digital transformation efforts. Policy makers can establish more efficient supportive programs targeted at environmental capability creation, not general digital uptake. The broad use in all kinds of industries shows that reason-based principles are widely applicable regardless of industry context.